Anthracycline-induced arrhythmias in breast cancer therapy: A meta-analysis of single-arm trials. - Tao Ran; Jinyao Chen; Qiurui She; Yi Mu; Min Zhang; Min Mao; Zhong Zuo; Juan Li (PLoS ONE)
Introduction As of 2020, breast cancer has emerged as the predominant cause of cancer incidence globally. Anthracycline-based chemotherapy serves as a crucial element in the treatment regimen for breast cancer. However, these anthracycline-based drugs are associated with cardiac toxicity. This study represents the first clinical quantitative analysis aimed at accurately determining the incidences of arrhythmia and abnormal electrocardiogram (ECG) changes, thereby providing valuable data to bolster clinical drug usage and monitoring. Methods A systematic search was conducted across multiple databases including CNKI, VIP, Wanfang, PubMed, Embase, Web of Science, and the Cochrane Library. The incidence of combined arrhythmias in breast cancer patients and the associated heterogeneity were calculated using either a random effect model or a fixed effect model. Statistical analysis was performed using STATA16. Results The study encompassed a total of 37 articles, which included 5705 breast cancer patients undergoing anthracycline treatment. Among these patients, 2257 developed arrhythmias. The meta-analysis revealed that the incidence of anthracycline-associated arrhythmias and abnormal ECG changes in breast cancer patients was 0.41 (0.37, 0.44). Subgroup analysis indicated that the incidence of ST-T segment change was 0.19 (0.15, 0.23), the incidence of conduction block was 0.04 (0.02, 0.05), the incidence of premature beats was 0.09 (0.07, 0.11), and the incidence of atrial fibrillation was 0.04 (0.00, 0.12). Additional results are presented in Table 3. Conclusion This pioneering study accurately assesses the incidence of arrhythmias in breast cancer patients treated with anthracyclines. The findings provide clinicians with valuable insights into understanding and managing the cardiac toxicity associated with such treatment. Moreover, this study lays the foundation for future research exploring the mechanisms underlying these arrhythmias and potential preventative strategies.